Course and outcomes of COVID-19 in patients with immunoinflammatory rheumatic diseases: Preliminary data from the NIIR/APP-COVID-19 registry and literature review - E. L. Nasonov; B. S. Belov; A. M. Lila; E. S. Aronova; G. I. Gridneva; A. V. Kudryavtseva; E. V. Sokol; A. V. Torgashina; I. B. Vinogradova; D. I. Abdulganieva; A. Yu. Zimenko (Научно-практическая ревматология)
The materials of the Russian NIIR/ARP-COVID-19 database, which included adult (over 18 years old) patients with immuno-inflammatory rheumatic diseases (IIRD) who underwent COVID-19 (coronavirus disease 2019), and a literature review concerning the course and outcomes of COVID-19 in patients with these diseases, are presented. From July 17, 2020 to April 23, 2021, 156 messages were received and analyzed. The study group was represented mainly by women (75%). The average age of patients was 52.0±14.8 years, of which 53 (33.9%) patients were aged 60 years and older. The most frequent clinical manifestations of COVID-19 were fever (62.2%), cough (40.4%), anosmia (37.8%), shortness of breath (33.3%). During the course of COVID-19, computed tomography of the chest organs was performed in 143 patients. When assessed on an “empirical” visual scale, stage 0 of lung lesion was observed in 49 (34.3%) patients, stage 1 in 40 (28%), stage 2 in 35 (24.5%), stage 3 in 19 (13.2%), stage 4 in 0. In the study group, a favorable outcome was observed in 137 (97.9%) patients. Fatal outcome was registered in 3 patients. The effect of COVID-19 on the course of IIRD was assessed in 131 patients: in 52 (39.7%) patients, the course of IIRD worsened, in 1 (0.8%) it improved, in 78 (59.5%) there was no effect. Literature data on the risk of infection with the SARS-CoV-2 virus, the course and outcomes of COVID-19 in rheumatic and musculoskeletal diseases are contradictory, which dictates the need to continue collecting data on the rheumatological problems of COVID-19 in the Russian patient population, taking into account international experience.